Mapping the evolution of density in 3D of thermally oxidised graphite for nuclear applications - Babout, L; Marrow, T; Mummery, P; Withers, P (2006)
This paper deals with the use of X-ray tomography and subsequent kernel operations on the reconstructed images to generate 3D density maps and phase labelling of polygranular graphite subjected to thermal oxidation which, in some respects, simulates radiolytic oxidation. This shows the suitability of the procedures to quantify density variations in oxidised samples. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.